Spectroscopic and Superparamagnetic Behaviour of Hausmannite Manganese Oxide Nanoparticles - Karpagavalli, S.; Kennady Vethanathan, S. John; Perumal, S. (Asian Journal of Chemistry, 2019)
Hausmannite manganese oxide (Mn3O4) nanoparticles are synthesized by microwave assisted solvothermal method. The calcination temperature of manganese oxide was determined from TG-DTA analysis.The structural characteristics of as prepared Mn3O4 nanoparticles are analyzed by powder X-ray diffraction. The Fourier transform infrared analysis is used to identify molecular structural changes of the manganese oxide sample. The SEM images revealed the surface morphology of the Mn3O4 nanoparticles and determined the size of the particle to be in the range of 30-40 nm. UV-visible spectrum showed that pure Mn3O4 nanoparticle exhibits maximum absorption at 396 nm. The cyclic voltammetry studies are used to evaluate specific capacitance and electrochemical behaviour of Mn3O4 nanoparticles. The magnetic properties of Mn3O4 nanoparticles are examined by vibrating sample magnetometer.